Viral gastroenteritis in Tocantins, Brazil: characterizing the diversity of human adenovirus F through next-generation sequencing and bioinformatics. (12th December 2020) - Tahmasebi, Roozbeh; Luchs, Adriana; Tardy, Kaelan; Hefford, Philip Michael; Tinker, Rory J.; Eilami, Owrang; de Padua Milagres, Flavio Augusto; Brustulin, Rafael; Teles, Maria da Aparecida Rodrigues; dos Santos Morais, Vanessa; Moreira, Carlos Henrique Valente; Buccheri, Renata; et al.
Abstract : Human enteric adenovirus species F (HAdV-F) is one of the most common pathogens responsible for acute gastroenteritis worldwide. Brazil is a country with continental dimensions where continuous multiregional surveillance is vital to establish a more complete picture of the epidemiology of HAdV-F. The aim of the current study was to investigate the molecular epidemiology of HAdV-F using full-genome data in rural and low-income urban areas in northern Brazil. This will allow a genetic comparison between Brazilian and global HAdV-F strains. The frequency of HAdV-F infections in patients with gastroenteritis and molecular typing of positive samples within this period was also analysed. A total of 251 stool samples collected between 2010 and 2016 from patients with acute gastroenteritis were screened for HAdV-F using next-generation sequencing techniques. HAdV-F infection was detected in 57.8 % (145/251) of samples. A total of 137 positive samples belonged to HAdV-F41 and 7 to HAdV-F40. HAdV-F40/41 dual infection was found in one sample. Detection rates did not vary significantly according to the year. Single HAdV-F infections were detected in 21.9 % (55/251) of samples and mixed infections in 37.4 % (94/251), with RVA/HAdV-F being the most frequent association (21.5 %; 54/251). Genetic analysis indicated that the HAdV-F strains circulating in Brazil were closely related to worldwide strains, and the existence of some temporal order was not observed. This is the first large-scale HAdV-F study in Brazil in which whole-genome data and DNA sequence analyses were used to characterize HAdV-F strains. Expanding the viral genome database could improve overall genotyping success and assist the National Center for Biotechnology Information (NCBI)/GenBank in standardizing the HAdV genome records by providing a large set of annotated HAdV-F genomes.